Faktor-Faktor yang Mempengaruhi Kepuasan, Loyalitas, dan Kepercayaan Pelanggan pada E-Commerce Shopee - Agustian Burda; Ambar Tyas Kusumo (Universitas YARSI, 2022)
The purpose of this study is to examine the impact of price, discount, free shipping, product quality, service quality, user safety, and perceived usefulness on consumer satisfaction, loyalty, and trust in Shopee e-commerce. This study employed the Structural Equation Model-Partial Least Square (SEM-PLS) approach with the SMART PLS 4.0 software. To obtain a research sample of 140 individuals, the sample is decided through random sampling. User satisfaction is affected by discounts, free shipping, and perceived usefulness, according to the study's findings. Where consumer pleasure has an impact on customer loyalty and confidence. Additionally, it is established that loyalty influences user trust